Two-stage bone-and-strut technique in the treatment of septic non-unions in the upper limb - Luigi Meccariello; Ante Prkić; Vincenzo Campagna; Alberto Serra; Vincenzo Piccinni; Denise Eygendaal; Michele Bisaccia; Giuseppe Pica; Andrea Schiavone; Giuseppe Rollo (Medicinski glasnik, 2021)
Aim To report the results of a two-stage reconstruction of septic non-unions of the upper limb using the bone-and-strut technique with a follow-up of more than two years. Methods A total of 19 patients (12 males and seven females; age 27 to 85 years) were included in this cohort study. The evaluation endpoint was set at 24 months. Radiographic union, Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) scores, pain and return to work were assessed. All patients were treated with debridement and antibiotic therapy. At a second stage, the non-union focus was filled with a cancellous bone allograft. Stability was provided using a locking plate and a bone strut. Results After 24 months, the QuickDASH scores improved from a median of 28 (interquartile range, 13 – 35 points), to a median of 78 (interquartile range, 70 – 89 points). Mean pain scores improved from 8.1 (range, 0.3-10) to 0.6 (range 0-2). Radiographic and clinical union was seen in all patients. The majority of patients returned to work or previous activities when retired. A new neurological deficit, recurrence of infection, or other surgery-related adverse events were not observed. Conclusion The two-stage bone-and-strut technique is a safe and effective technique in the treatment of septic non-unions of the upper limb. The union rate is high, the complication rate is acceptable and return return-to-work is high. Recurrence of infectious sequelae during a follow-up period of at least two years was not seen. The patient-reported outcomes increased significantly.
Keywords: fractures; ununited; infections; surgical procedures; operative